Determinants of Financial Performance of Commercial Banks in Kenya - Ongore, Vincent Okoth; Kusa, Gemechu Berhanu (International Journal of Economics and Financial Issues, 2013)
Studies on moderating effect of ownership structure on bank performance are scanty. To fill this glaring gap in this vital area of study, the authors used linear multiple regression model and Generalized Least Square on panel data to estimate the parameters. The findings showed that bank specific factors significantly affect the performance of commercial banks in Kenya, except for liquidity variable. But the overall effect of macroeconomic variables was inconclusive at 5% significance level. The moderating role of ownership identity on the financial performance of commercial banks was insignificant. Thus, it can be concluded that the financial performance of commercial banks in Kenya is driven mainly by board and management decisions, while macroeconomic factors have insignificant contribution. Keywords: Financial Performance; Bank Specific Factors; Macroeconomic Variables JEL Classifications: E4; G2